A large outbreak of Legionnaires’ Disease in an industrial town in Portugal - George, Francisco (2016)
Background: We describe the investigation and control of an outbreak of Legionnaires’ disease in Portugal in October, November and December 2014. Methods: Confirmed cases were individuals with pneumonia, laboratory evidence of Legionella pneumophila serogroup 1 and exposure, by residence, occupational or leisure to the affected municipalities. 49 possible sources were reduced to four potential sources, all industries with wet cooling system, following risk assessment. We geo-referenced cases’ residences and the location of cooling towers defining four study areas 10km buffer centered on each cooling tower system. We compared the number of cases with expected numbers, calculated from the outbreak's attack rates applied to 2011 census population. Using Stones’ Test, we tested observed to expected ratios for decline in risk, with distance up to 10km four directions. Isolates of Legionella pneumophila were compared using molecular methods. Results: We identified 403 cases, 377 of which were confirmed, 14 patients died. Patients became ill between 14 October and 2 December. A NE wind and thermal inversion were recorded during the estimated period of exposure. Disease risk was highest in people living south west from all of the industries identified and decreased with distance (p<0.001). 71 clinical isolates demonstrated an identical SBT profile to an isolate from a cooling tower. Whole genome sequencing identified an unusual L. pneumophila subsp. fraseri serogroup 1 as the outbreak causative strain, and confirmed isolates’ relatedness. Conclusions: Industrial wet cooling systems, bacteria with enhanced survival characteristics and a combination of climatic conditions contributed to the second largest outbreak of Legionnaires’ disease recorded internationally.